Comparison of meshing characteristics and dynamic behavior of hypoid gear drive under different load conditions - Xiaole Wang; Yang Yang; Jianwei Lu; Xianguang Gu; Shaowu Qiu; Jianxue Liu; Zhining Zhang; Baobao Dai (Advances in Mechanical Engineering)
The study of loaded meshing characteristics and dynamic behavior is significant for evaluating the stability of hypoid gear under actual working conditions. Loaded tooth contact analysis (LTCA) of a hypoid gear drive under different loads is carried out. The equivalent meshing force, loaded transmission error (LTE), comprehensive elastic deformation, and time-varying meshing stiffness (TVMS) are investigated. Results show that the LTE and TVMS are sensitive to load, and the LTE and TVMS curves show obvious asymmetric as the load increases. Under low load conditions, the actual contact ratio increases significantly with the increase of load, but tends to be flat when the load reaches a certain range. The obtained TVMS and LTE are fitted by higher Fourier series and introduced into an 8-DOF dynamic model. By comparing the time history diagram, phase diagram, Poincaré section, and spectrum, the dynamic characteristics of the system under different loads are contrasted. On low load condition, the system may exhibit chaotic motion in certain meshing frequency bands and damping ratio intervals. While the tooth backlash increases to a critical value, the system may change to chaotic motion from periodic motion. The results provided a basis for improving the meshing performance of hypoid gear.